Порівняльний аналіз експериментальних та результатів імітаційного моделювання роботи автономної вітроелектричної установки з асинхронним генератором з використанням імпульсного пристрою для зарядження акумуляторних батарей - Головко, В. М.; Сандовал, К. Р. (Енергетика і автоматика, 2017)
COMPARATIVE ANALYSIS OF EXPERIMENTAL AND SIMULATION OF THE AUTONOMOUS simulation of wind power installations with asynchronous generators USING PULSE device for charging batteries V. M. Golovko, K. R. Sandoval The use of autonomous systems with asynchronous wind generator for its simplicity of design, high reliability is one of the efficient ways for remote power supply from the central system users. Using asynchronous machine as generator reactive power demands submission to the stator winding for self-excitation, which is often made from block capacitors. The aim of study was a comparative analysis of the efficiency of wind power battery systems with asynchronous generator and pulse converter for charging batteries on indicators obtained on the basis of simulation and experiment. For this experimental stand was developed, consisting of the following elements: wind power plant with an asynchronous generator, three-phase rectifier pulse converter and the load (battery). Control switching key by using pulse-width modulation with an operating frequency of 2 to 10 Hz. The research program was supposed to determine the influence of the pulse duty cycle of the converter weekend performance induction generator wind turbines at different wind speeds below par in the range of 0.95 to 0.75 / The analysis shows that the change in duty cycle of 0.2 to 0.9 asynchronous machine loses generator mode by changing wind speeds in the range of 0.95 - 0.75 of the nominal value. The discrepancy between the values obtained by experiment and model, is between 3 and 5%, indicating its adequacy.